Model of Theory Writing for Applied Master Thesis Based on Genre - Nur Hasyim; Ade Sukma Mulya; Abdillah Abdillah; Darul Nurjanah (Politeknik Negeri Padang, 2018)
The Theory section of the applied master thesis is not easy to write. Research that has investigated the writing efforts and strategies for these parts is also not found. Therefore, this article presents a theoretical part writing model in a genre-based applied master thesis. This model is the result of research conducted with a development research approach. The result is (i) the main needs that need to be written in this section are to describe the theory so that this section needs to be written on the basis of text and report descriptions, (ii) description is the type of text that explains something as it really is; the structure of the description text is (a) something that is explained, (b) part of something described, (iii) report is a type of text that classifies something in its class; Report text structure is (a) things that must be reported, (b) classes / subclasses, (iv) description texts and report texts have linguistic characteristics that are used that need to be referenced so that the author is able to write the theory section correctly and quickly